FUTURISTIC SCPOPE OF BIOMARKERS IN TUBERCULOSIS - PREETI, SHARMA; Pradeep, Kumar; RACHNA, SHARMA; KUMAR, ARORA VIJAY (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT One of the major causes of the mortality from single infectious agent, tuberculosis (TB) is prevalent worldwide. India has the highest number of TB cases in the world. It is the leading cause of death, because of its high mortality and morbidity because of the disease. Reason lies in the emergence of multidrug-resistant TB strains, and the HIV infection, which reactivates the latent TB making it more severe. Moreover, failure to diagnose TB early remains one of the primary hurdles in controlling of the disease. TB is a potentially hazardous infectious disease attacks various organs, mainly affecting lungs. The bacteria causing TB are spread from one person to another. Tiny droplets released into the air via coughs and sneezes lead to the passage of infection. The disease is generally diagnosed by its symptoms, radiographic methods, and sputum smear microscopy and by cultivation of the Mycobacterium tuberculosis, which is considered as gold standard. Current advances in molecular biology and molecular epidemiology and a better understanding of drug resistance in TB have given a new horizon to its rapid diagnosis. However, the cost-effective techniques, and their requirement for sophisticated equipment and skilled personals have excluded their implementation on a routine basis, especially in low-income countries. Keywords: Biochemical markers, Tuberculosis, Microbiological tuberculosis.